Chloroquine cardiomyopathy – a review of the literature. (June 2013) - Tönnesmann, Ernst; Kandolf, Reinhard; Lewalter, Thorsten
Abstract Chloroquine and hydroxychloroquine are still used for the prevention and treatment of malaria. Moreover, they are experiencing a renaissance in the long-term therapy of connective tissue diseases (particularly in systemic lupus erythematosus). They induce a lysosomal dysfunction with an accumulation of pathologic metabolic products, which can be seen in ultrastructural histology as pathognomonic cytoplasmic inclusion bodies. Due to its lower toxicity, hydroxychloroquine is the form used predominantly today. Retinopathy as a toxic result of this medication is well known. Cardiac side effects are rarely reported, but in some cases can be severe and irreversible – two cases of organ transplantation have been described in the literature. They comprise conduction disturbances (bundle-branch block, atrioventricular block) and cardiomyopathy – often with hypertrophy, restrictive physiology and congestive heart failure. As the clinical features of cardiotoxicity are unspecific, the identification and follow-up of potentially affected patients is of utmost importance. Confirming the diagnosis of this toxic storage disease requires histological examination of the myocardium in conjunction with electron microscopy. The primary clinical parameters (diagnostic criteria for this cardiomyopathy, differential diagnostics, incidence, risk factors, prognosis) as well as the diagnostic procedures are discussed against the background of the available literature.